Effect of Umbelliprenin on HIF-1α- Driven Angiogenesis Induced by EGF and CoCl2 in T47D Cell Line - Somayeh Mahmoodi Khatonabadi; Roya Atabakhshian; Reza Mirfakhraie; Shiva Ghafghazi; Seyed Ali Ziai* (Iranian Society of Pharmacognosy, 2024)
Background and objectives: Breast cancer is a highly common cancer that affects women worldwide. Different forms of breast cancer are currently treated using various strategies. One successful avenue in cancer therapy involves targeting anti-angiogenic factors. Extensive evidence supports the idea that umbelliprenin, a natural compound derived from plant species, possesses anti-cancer properties. In this research, we investigated the impact of umbelliprenin on the PI3K/AKT/mTOR and PI3K/AKT/MAPK signaling pathways, along with their downstream products HIF-1α/VEGF, within the T47D cell line. Methods: We assessed the cytotoxic effects of umbelliprenin on T47D cell lines using the MTT method. Non-toxic concentrations, specifically IC5 and IC10 of umbelliprenin, were selected to investigate the effects on the signaling pathways. For T47D cells stimulated by EGF and cobalt chloride (CoCl2), we measured the mRNA levels of EGFR, PI3K, AKT, mTOR, S6K, HIF-1β, HIF-1α, VEGF, VEGFR, ERK1/2, and 4EBP1 using Real-time PCR. Additionally, we examined VEGF and HIF-1α protein expression through Western blot analysis. Results: We determined that the IC5 and IC10 concentrations of umbelliprenin were 10 and 20 µM, respectively, using the MTT method. Umbelliprenin significantly reduced the expression of VEGF and HIF1-α proteins in cells stimulated with EGF and CoCl2. It also led to a decrease in the mRNA levels of EGFR, PI3K, VEGF, mTOR, HIF1-α, HIF-1β, S6K, ERK2, and ERK1. Conclusion: The results of this study indicated that umbelliprenin, functioning as a cytotoxic agent, inhibits the PI3K/AKT/mTOR and PI3K/AKT/MAPK signaling pathways in T47D cells induced by EGF and CoCl2.